Structural displacement estimation using accelerometer and FMCW millimeter wave radar. (1st January 2023) - Ma, Zhanxiong; Choi, Jaemook; Yang, Liu; Sohn, Hoon
Highlights: Collocated FMCW mmWave radar and accelerometer for structural displacement estimation. Automated estimation of the best target for the radar. Adaptive phase-unwrapping algorithm using acceleration measurement. Automated direction conversion for the estimated displacement. Abstract: Structural displacement plays a crucial role in structural health monitoring. However, its measurement remains challenging for many civil infrastructure applications. This study proposes a structural displacement estimation technique that fuses measurements from a collocated accelerometer and frequency-modulated continuous-wave millimeter wave radar at displacement estimation location on a structure. Automated initial calibration was first performed using short-period (less than 1 min) radar and acceleration measurements. The best target is automatically selected from the surroundings, and a conversion factor to convert the line-of-sight displacement to the structural displacement in the actual vibration direction is automatically estimated for the target. After calibration, the displacement is estimated in real time from radar measurements using the selected best target and its estimated conversion factor. Note that an accelerometer-aided phase-unwrapping algorithm is proposed and applied to address the phase-wrapping issue when the structural displacement is larger than the radar wavelength. The radar-based displacement is further fused with the acceleration measurement using a finite impulse response filter to estimate the displacement with improved accuracy at the cost of a short time delay. Laboratory tests on a four-story building model and a field test on a pedestrian bridge were conducted to validate the proposed displacement estimation technique. The displacements estimated by the proposed technique had an error of less than 1 mm in both tests compared to the ground-truth displacements measured by laser-based displacement sensors.